Effect of Early Secreted Antigen Target-6 Gene of Mycobacterium Tuberculosis as Genetic Adjuvant for Avian Influenza Virus DNA Vaccine in Chickens - Oveissi, Sara (2009)
Influenza virus, belongs to the family Orthomyxoviridae and genus Influenza virus A, causes major disease problems and serious economical losses in poultry industry. Highly pathogenic avian influenza H5N1 subtype which is associated with acute infection with high morbidity and mortality in susceptible birds, is still enzootic in poultry in Asia as well as European and African countries. The virus may also possess serious threat to the emergence of influenza pandemic in humans. Vaccination is one of the biosafety measures which has the greatest impact on improving global health and preventing morbidity and mortality due to avian influenza (AI) infection. The explosion of knowledge in molecular immunology has paved radical developments in vaccine technology. Immunization with DNA vaccines and genetic adjuvants as immunostimulators is an attractive approach in the development of future generations of vaccines and adjuvants. The viral envelope proteins, hemagglutinin (HA or H) and neuraminidase (NA or N), have been shown to play key roles in triggering protective immune responses against AI infection. Meanwhile, nucleocapsid protein (NP) may play a central role in cross protection between AI virus serotypes. The Mycobacterium tuberculosis Early Secreted Antigenic Target-6 (ESAT-6) antigen has been shown to elicit both humoral and cellular immunity, thus it has an ability to act as a genetic adjuvant. This study examined the ability of ESAT-6 to modulate antibody response against H5 following vaccination with DNA vaccine in chickens. In order to study the immunological properties of AIV DNA vaccines, several recombinant plasmids pcDNA3.1/H5, pcDNA3.1/N1, pcDNA3.1/NP, pcDNA3.1/H5-ESAT6, pcDNA3.1/N1-ESAT6 and pcDNA3.1/NP-ESAT6 were constructed. The recombinant plasmid constructs were confirmed by restriction enzymes and sequence analyses. The expression of genes of interest in cell culture was confirmed by immunofluorescence test and Western blot analysis. The immunogenicity of the DNA vaccine pcDNA3.1./H5 with and without the presence of ESAT-6 in specific-pathogen-free (SPF) chicks was determined. Sera obtained from the chickens immunized with pcDNA3.1/H5 and pcDNA3.1/H5-ESAT6 demonstrated viral neutralizing activities based on haemagglutination inhibition (HI) test. The sera collected from chicks immunized with pcDNA3.1/H5-ESAT6 have higher HI titer compared to the group which was immunized with pcDNA3.1/H5. However, the increase in HI titer at different post immunization days between these groups was not statistically significant. When the tissue samples from the chest muscle of injection site and spleen from chickens immunized with the DNA vaccine were analyzed by reverse transcriptase polymerase chain reaction (RT-PCR), all the samples were positive for H5 specific transcripts. In summary, the current study delineated that the constructed recombinant plasmids were transcriptionally active in the in vivo chicken model and DNA immunization in SPF chicks with pcDNA3.1/H5 and pcDNA3.1/H5-ESAT6 produced humoral immune response. In conclusion, future studies are required to explore the role of ESAT-6 gene of Mycobacterium tuberculosis as an effective genetic adjuvant for H5 DNA vaccine in chickens.